Outcome following surgical repair of achilles tendon rupture and comparison between postoperative tibiotarsal immobilization methods in dogs - Nielsen, C.; Pluhar, G. E. (Veterinary and Comparative Orthopaedics and Traumatology, 2006)
Surgical treatment of Achilles tendon rupture in dogs is generally associated with a favourable outcome, although the recovery time to best function is relatively long at 20.2 weeks. Dogs with injuries of less than 21 days duration may have a better functional outcome. When comparing external fixator application to splint or cast management, initial tibiotarsal immobilization method does not significantly affect the complication rate, duration of immobilization, recovery time, or functional outcome.
Keywords: Achilles tendon; surgery – tendon; joint immobilization